2020
DOI: 10.1007/s11356-020-10562-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on CO2 absorption and physicochemical characteristics of different carbon-loaded aqueous solvents

Abstract: The anthropogenic carbon dioxide (CO 2 ) denseness in the earth's atmosphere is increasing day-to-day by combusting fossil fuels for power generation. And, it is the most important greenhouse gas (GHG) responsible for 64% of global warming. Solvent-based carbon capture gained more attention towards researchers because of its easiness to integrate with the coal-fired power plant without significant modifications. During CO 2 absorption, the physical property of the solvent gets changed. A change in the solvent'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…A similar behaviour was also reported earlier. [41][42][43] From this study, it was also observed that [TBA][Br] exhibits higher reaction mixture temperature when compared to [TBA][OAC] in solvent blends. Higher the reaction mixture temperature may lower the viscosity of solvent blends during absorption.…”
Section: Variation Of Reaction Mixture Temperature During Absorptionsupporting
confidence: 56%
See 1 more Smart Citation
“…A similar behaviour was also reported earlier. [41][42][43] From this study, it was also observed that [TBA][Br] exhibits higher reaction mixture temperature when compared to [TBA][OAC] in solvent blends. Higher the reaction mixture temperature may lower the viscosity of solvent blends during absorption.…”
Section: Variation Of Reaction Mixture Temperature During Absorptionsupporting
confidence: 56%
“…The constant 0.5Psig pressure of CO 2 inlet gas is passed into the reactor containing solvent blends until the solution reaches saturation. [41][42][43] During absorption process, CO 2 loaded solution was withdrawn at various time intervals and the carbon loading was measured with the help of Chittick apparatus. 41 Physicochemical properties such as pH, solubility of CO 2 (carbon loading), density, surface tension and viscosity were measured before and after completion of the absorption process.…”
Section: Materials Requiredmentioning
confidence: 99%
“…All of the basic physicochemical properties of the solvent and CO 2 absorption exhibit interdependent eccentrics. 29 An exhaustive review of the literature reveals that researchers had studied binary mixtures of NVP with water, 7 alcohols, 30 and ionic liquids, 31,32 DEGMEE with N,N-dimethylformamide, 33 ionic liquids, 34 alcohols, 35,36 etc., DEGMBE with water, 37 amines, 38 alcohols, 39 etc., as well as mixtures of TEGMME with water, 40 alcohols, 41 and Nmethyldiethanolamine. 42 But to the best of our knowledge, no literature is available for binary mixtures of NVP with DEGMEE, DEGMBE, and TEGMME, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] During the chemical absorption process, the solvent significantly influences CO 2 capture performance. [8][9][10][11] Amine solutions, such as monoethanolamine, methyldiethanolamine (MDEA), 2-amino-2-methyl-1-propanol (AMP)/piperazine solution, and mixture amines, are conventional solvents used to capture CO 2 . In order to characterize the performance of the amine solutions, mathematical modeling analysis and experiment analysis have been usually employed to predict the reaction mechanism, CO 2 fraction distribution, and temperature variation trend.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical absorption has been developed as one of the most promising methods for industrial CO 2 capture 2‐7 . During the chemical absorption process, the solvent significantly influences CO 2 capture performance 8‐11 …”
Section: Introductionmentioning
confidence: 99%